2021
DOI: 10.1093/jeea/jvab039
|View full text |Cite
|
Sign up to set email alerts
|

“Marshall Lecture 2020: The Measure of Monopsony”

Abstract: There has been increasing interest in recent years in monopsony in labour market. This paper discusses how we can measure monopsony power combining insights from models based on both frictions and idiosyncrasies. It presents some evidence from the UK and the US about how monopsony power varies across the wage distribution within markets, over the business cycle and over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…Hence, our findings suggest that even for low-skilled would-be migrants in low-income countries, any migration-enhancing liquidity effects of rising incomes are more than offset by migration-reducing incentive effects through falling income gaps. The estimates are complementary to the results reported by Langella and Manning (2021), who also found a negative relationship across income groups when focusing on migration aspirations. The switch from a positive to a universal negative relationship we observe when controlling for cross-country heterogeneity is in line with what several previous studies have found (e.g.…”
Section: Baseline Specificationcontrasting
confidence: 93%
“…Hence, our findings suggest that even for low-skilled would-be migrants in low-income countries, any migration-enhancing liquidity effects of rising incomes are more than offset by migration-reducing incentive effects through falling income gaps. The estimates are complementary to the results reported by Langella and Manning (2021), who also found a negative relationship across income groups when focusing on migration aspirations. The switch from a positive to a universal negative relationship we observe when controlling for cross-country heterogeneity is in line with what several previous studies have found (e.g.…”
Section: Baseline Specificationcontrasting
confidence: 93%
“…Our preferred estimate of the wage elasticity of quits, which disregards the two outlier coefficients at the tails, is −0.36. This estimate is very close to the main separation elasticities reported by Langella and Manning (2021) for the comparable US (−0.31) and UK (−0.37) data.…”
Section: Channelssupporting
confidence: 86%
“…Taken together, we conclude that regional and sectoral restrictions and prioritization are associated with a lower wage elasticity of quits, consistent with the prediction from monopsonistic models. While the estimated elasticities do not have a causal interpretation since we do not have exogenous variation in the wage at the firm level, as in Langella and Manning (2021), our interest lies less in the estimate of the level of the elasticity as such but in the comparison by policy environment. If the biases are constant, then the conclusions about this variation could be valid even if the level is not.…”
Section: Channelsmentioning
confidence: 97%
See 1 more Smart Citation
“…3. See Posner et al (2018) on USA, Langella and Manning (2021) on UK, Araki et al (2022) on OECD. Manning (2020) offers a thorough review of the issues and evidence pertaining to the exercise of labour market power by firms.…”
mentioning
confidence: 99%